(untitled) (Письма в ЭЧАЯ, 2024)
This paper explores the dynamics of a two-dimensional Kemmer oscillator (KO) in a non-commutative phase space within the framework of relativistic quantum mechanics. We obtainthe eigenstates of the system and investigate the influence of non-commutative parameterson these solutions.